How female collagiate gymnasts generate a double twist in the backward stretched somersault - Rieko, H.; Michiyoshi, A.; Kazumichii, A.; Yu, K.; Sayaka, A.; Yoshiaki, H.; Kyoko, S. (ISBS Proceedings Archive (Michigan), 2019)
The purposes of this study were to describe how female gymnasts generate a double twist in the backward stretched somersault and to draw suggestions to improve twist techniques of female gymnasts by analysing female gymnasts twist motion three-dimensionally. Three varsity female gymnasts performed thebackward stretched somersault with a double twist several times and were motion-captured with a Vicon system (250 Hz). The angular velocities and angular momenta of the body segments and whole bodywere calculated, based on the Tang`s method. The female gymnasts of the contact-type twisted the trunk, especially the upper torso largely before the aerial-type onelaterallyflexed her trunk after the toe-off with her right arm swinging down.For female gymnasts who intend to gain larger twist angular momentum or increase it, it is recommended to quickly move the opposite arm and twist the upper torso toward the twist direction during the take-off phase.